2021
DOI: 10.1038/s41598-021-96986-1
|View full text |Cite
|
Sign up to set email alerts
|

A universal vaccine candidate against Plasmodium vivax malaria confers protective immunity against the three PvCSP alleles

Abstract: Malaria is a highly prevalent parasitic disease in regions with tropical and subtropical climates worldwide. Among the species of Plasmodium causing human malaria, P. vivax is the second most prevalent and the most geographically widespread species. A major target of a pre-erythrocytic vaccine is the P. vivax circumsporozoite protein (PvCSP). In previous studies, we fused two recombinant proteins representing three allelic variants of PvCSP (VK210, VK247 and P. vivax-like) to the mumps virus nucleocapsid prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…In agreement, Montanide triggered higher cytophilic-type IgG titers (IgG2b) and was able to generate antibodies with higher avidity than those elicited by Poly (I:C). These differences could explain the higher partial protection against the challenge that Montanide conferred when administered with a PvCSP-based antigen ( 10 ). However, the protection achieved was not sterile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement, Montanide triggered higher cytophilic-type IgG titers (IgG2b) and was able to generate antibodies with higher avidity than those elicited by Poly (I:C). These differences could explain the higher partial protection against the challenge that Montanide conferred when administered with a PvCSP-based antigen ( 10 ). However, the protection achieved was not sterile.…”
Section: Discussionmentioning
confidence: 99%
“…One of them, Poly (I:C), elicited high antibodies titers conferring partial protection to immunized mice ( 6 , 8 , 9 ). Another adjuvant tested in our formulations was Montanide ISA 720, which generated even higher IgG titers and promoted a greater decline in parasite burden during the challenge test when compared to Poly (I:C)- adjuvanted formulations ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although VK210 is the most common variant of PvCSP 22 , the expression of only this sequence on the Pb platform may represent a limitation of PbviVac. In fact, a recombinant protein including the repeats of both PvCSP VK210 and VK247, as well as of P. vivax-like CSP, has recently been generated and shown to elicit the production of high titers of antibodies against each of the variants following immunization of a mouse model 45 . Accordingly, and since previous studies demonstrated the absence of significant cross-reactivity among the different PvCSP alleles in animals immunized with individual recombinant proteins (VK210, VK247 and P. vivax-like) 46 , the Pb platform may in the future be engineered to simultaneously express of the most common alleles of CSP, potentially eliciting protective immune responses against a wider range of Pv strains.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with recombinant CS protein in Montanide ISA-720 induced high and long-lasting antibody responses and partial protection against challenge with parasites in mice. 64 Immunization with recombinant CS protein in Montanide ISA-51 is tested in malaria-naïve and semi-immune volunteers in an ongoing trial (NCT04739917, Table 1).…”
Section: Vaccine Platforms In Which Ifa Has Been Used With Advantage ...mentioning
confidence: 99%